Encouraging exclusivity: The electoral system and campaigning in the 1999 South African Election - Davis, Gavin (Department of Political Studies, 2014)
This dissertation provides an analysis of the 1999 election campaign and considers how each of the main parties appealed to the politically salient groups in South Africa. The case is put forward that the electoral system--closed-list proportional representation-rewards parties that appeal to a particular race group (or groups) at the expense of others. Parties that adopt a conciliatory tone and attempt a 'catch-all' strategy are punished at the polls. The persistence of this phenomenon means that politics in South Africa is likely to remain racialised, as political entrepreneurs maximise votes by making narrow sectional appeals.